Effect of para-chlorophenylalanine on hormonal profile in anestrus buffaloes - SINGH, J K; LUDRI, R S (The Indian Journal of Animal Reproduction, 2008)
Parachlorophenylalanine (PCPA), when administered intra-peritoneally (I 00mg/kg body wt., 1/P) is effective in reducing the level of prolactin(PRL) to certain extent by inhibiting serotonin biosynthesis in an estrus buffaloes. 5-hydroxytryptophan (5-1 ITP) (I mg/kg/body wt., 1/M.) induces prolactin release by restoring serotonin biosynthesis. Level of prolactin increased about three folds as compared to pre-treatment levels and more than 1 O folds as compared to PRL level at 32 hr after PCPA treatment. These compounds have effect on cortisol level of which showed fluctuations while as LH levels remain more or less unaffected. These compounds do not improve anestrus condition in buffaloes